2018
DOI: 10.11604/pamj.2018.29.144.12301
|View full text |Cite
|
Sign up to set email alerts
|

Limited knowledge of diabetes in patients attending an outpatient diabetes clinic at a referral hospital in Zimbabwe: a cross-sectional study

Abstract: IntroductionDiabetes mellitus (DM) has increased globally, with a significant increase noted in African communities. Self-care health-related behavior is determined by beliefs about health and illness which are based on the person?s knowledge of diabetes. The present study aimed to assess patients' diabetes awareness and level of diabetes knowledge in Zimbabwean adults with diabetes attending an outpatient diabetes clinic at a main referral hospital.MethodsIn this cross-sectional descriptive study, the Diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 27 publications
8
24
1
Order By: Relevance
“…Another study performed in Zimbabwe also showed that a similar proportion of people (45%) reported consulting a diabetes educator at least once. 17 These figures compare favourably to reports from countries with more resources for DSME than Zimbabwe. 18 It must be noted that the scope and content of DSME interventions in most Zimbabwean clinics are not documented, nor do standards for DSME exist.…”
Section: Discussionmentioning
confidence: 63%
“…Another study performed in Zimbabwe also showed that a similar proportion of people (45%) reported consulting a diabetes educator at least once. 17 These figures compare favourably to reports from countries with more resources for DSME than Zimbabwe. 18 It must be noted that the scope and content of DSME interventions in most Zimbabwean clinics are not documented, nor do standards for DSME exist.…”
Section: Discussionmentioning
confidence: 63%
“…Knowledge has been documented as a key component to public health intervention such as SHAKE and REPLACE. Previous studies carried out in Zimbabwe among diabetic patients showed low levels of knowledge and awareness of this disease and the dietary needs for patients with the disease [15]. Hypertension is not prioritized in Zimbabwe and there is little awareness of appropriate diets for preventing or/and controlling it [16].…”
Section: Introductionmentioning
confidence: 99%
“…Patient knowledge regarding diabetes and its management, including self-management, can also be poor among patients with T2DM in Africa (Mogre et al, 2017;Bonger et al, 2018;Stephani et al, 2018;Moosa et al, 2019). This is exacerbated by low levels of education among patients attending PHC facilities in SSA with CVD including T2DM and hypertension; however, this is not universal (Moosa et al, 2015;Kassahun et al, 2016;Nashilongo et al, 2017;Rampamba et al, 2017;Mufunda et al, 2018;Chang et al, 2019;Moosa et al, 2019;Niguse et al, 2019). In addition, there are concerns that being overweight and obese is still seen as a sign of affluence in a number of African communities, although changing, and appreciable weight loss still has the stigma of HIV and acquired immune deficiency syndrome (AIDS) associated with it.…”
mentioning
confidence: 99%
“…However, such activities are not universal across Africa. Alongside this, there have been initiatives among African countries surrounding patient education and empowerment, along with support mechanisms such as the CCMDD initiative in South Africa, to improve access to treatment as well as adherence to suggested lifestyle changes and prescribed medicines (Ovbiagele, 2015;Kassahun et al, 2016;Jaam et al, 2017;Meyer et al, 2017;Amadi et al, 2018;Gathu et al, 2018;Mufunda et al, 2018;Stephani et al, 2018;Manne-Goehler et al, 2019;Rampamba et al, 2019). However, only a limited number of papers have been published assessing the impact of different initiatives in these patients (Sapkota et al, 2015;Gathu et al, 2018;Rampamba et al, 2019).…”
mentioning
confidence: 99%